Core values of sports teams: What are they and how are they conveyed? - Raisbeck, E. (Leadership Education Capstones, 2016)
The mission of this study is to understand what core values current coaches believe to be important within their programs. It is also intended to discover how these coaches convey each value to the members of their team. By identifying core values and outlining strategies for communication and implementation, future coaches andleaders can formulate their team`s identity. This study provides beneficial information on designing and implementing core valuesfor coaches who aspire to take on the leadership role of head coach. Coaches should contemplate which core values they believe in and how to convey those values to their team.